Diesel engine applications for evaluation of performance and emission behavior of biodiesel from different oil stocks - Behcet, Rasim; Aydin, Huseyin; Ilkilic, Cumali; Iscan, Bahattin; Aydin, Selman (Wiley-Blackwell, 2015)
Extensive researches on alternative fuels have been carried out since the fossil-based fuels are limited. Many of these studies have ever been on the usability of vegetable oils in diesel engines. In the current work, biodiesel were produced from waste fish oil (FOB), hazelnut oil (HOB), rapeseed oil (ROB), and waste cooking oil (WCOB) by transesterification method. The same optimized variables of 6:1 methanol/oil molar ratio (mol/mol), 0.4% sodium methoxide concentration (wt.%), 60 degrees C reaction temperature, 1000 rpm agitation speed and 2 h reaction time conditions were performed for biodiesel production from all kinds of above mentioned oils. Some of the important chemical and physical properties of test fuels were found. Without making blends with diesel fuel, pure biodiesels were used in a diesel engine in order to clarify how their usage effects on engine performance and exhaust emission parameters. When compared with those of diesel fuel, average torque and power were reduced while brake specific fuel consumption was increased for biodiesels. Besides, carbon monoxide (CO), hydrocarbon (HC) emissions were considerably lower for biodiesel usage while oxides of nitrogen (NOx) emissions were higher than that of diesel fuel. Furthermore, emissions of carbon dioxide (CO2) and smoke opacity were reduced for biodiesel usage. Oxygen (O-2) contained in the exhaust gases were higher for biodiesels while they contain more oxygen molecules in their structure. (c) 2014 American Institute of Chemical Engineers Environ Prog, 2014 34: 890-896, 2015
Keywords: biodiesel; diesel engine; emissions; engine performance